2009
DOI: 10.1037/a0014502
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of borderline personality features in population samples: Is the Personality Assessment Inventory–Borderline Features scale measurement invariant across sex and age?

Abstract: Borderline personality disorder (BPD) is more often diagnosed in women than in men, and symptoms tend to decline with age. Using a large community sample, the authors investigated whether sex and age differences in four main features of BPD, measured with the Personality Assessment InventoryBorderline Features scale (PAI-BOR; Morey, 1991), are a result of measurement bias or if they represent true differences. The PAI-BOR was completed by four Sex ϫ Age groups (N ϭ 6,838). Multigroup confirmatory factor analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
48
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 37 publications
5
48
0
1
Order By: Relevance
“…These two factors explained 50.03% of the total variance. Previous studies that examined the factor structure of borderline personality indicated that the structure of BPD in nonclinical and clinical samples can range from a one-factor to a six-factor [23][24][25][26][27]. In this present study, we found a one-dimensional solution when we examined the factorial structure and the content of the borderline personality by the Turkish BPQ.…”
Section: Discussionsupporting
confidence: 47%
“…These two factors explained 50.03% of the total variance. Previous studies that examined the factor structure of borderline personality indicated that the structure of BPD in nonclinical and clinical samples can range from a one-factor to a six-factor [23][24][25][26][27]. In this present study, we found a one-dimensional solution when we examined the factorial structure and the content of the borderline personality by the Turkish BPQ.…”
Section: Discussionsupporting
confidence: 47%
“…As a function of gender, some studies find that men score higher than women in BPD traits (Aggen et al, 2009;Trull, 1995), others find that women score higher than men (De Moor et al, 2009;Ekselius, Bodlund, von Knorring, Lindström, & Kullgren, 1996;Lipp, Arnold, & Siddle, 1994;Trull, 1995), while a third group of studies finds no differences (Gardner & Qualter, 2009b;Rawlings et al, 2001). In any case, although some men may score higher in several BPD traits, this does not mean that the prevalence of BPD is higher in men; on the contrary, the rates in clinical samples are two to three times higher in women (Widiger & Trull, 1993).…”
mentioning
confidence: 72%
“…In any case, although some men may score higher in several BPD traits, this does not mean that the prevalence of BPD is higher in men; on the contrary, the rates in clinical samples are two to three times higher in women (Widiger & Trull, 1993). With regard to age, mean levels of BPD traits are more higher in adolescence, and decline with age (Cohen, Crawford, Johnson, & Kasen, 2005;De Moor et al, 2009;Rawlings et al, 2001). Nevertheless, the phenotypic expression of the BPQ traits in nonclinical population and their relationship with gender and age require further research.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The DSM IV-TR makes no statement regarding sex bias among the PDs, but it does suggest that six disorders (antisocial, narcissistic, obsessive-compulsive, paranoid, schizotypal, schizoid) are more prevalent in men, and three others (borderline, histrionic, dependent) occur more in women (Jane et al, 2007). The diagnosis schizoid PD (SPD) is more common in men (Fulton and Winokur, 1993), whereas borderline PD (BPD) is more often diagnosed in women than in men (De Moor et al, 2009). A revised study using the data of over 40,000 individuals of the National Epidemiological Survey on Alcohol and Related Conditions resulted in a different sex distribution.…”
mentioning
confidence: 96%